Integrated-reservoir-model-based critical oil rate correlation for vertical wells in thin oil rim reservoirs in the Niger Delta - Ndarake Okon, Anietie; Appah, Dulu (International Journal of Engineering and Technology, 2018)
Thin oil rim reservoirs are mostly characterized by development and production challenges; one of which is early water coning tendency. In the Niger Delta, most developed critical oil rate correlations to avert coning focused on conventional bottom-water drive reservoirs, while thin oil rim reservoirs received limited attention. Available correlations to estimate critical oil rate of thin oil rim reservoirs in Niger Delta are based on generic reservoir models, which does not consider the reservoir heterogeneity. Hence, it leaves these available correlationsâ€™ predictions in doubt, considering the sensitive nature of developing thin oil rim reservoirs. Thus, a correlation for critical oil rate (qc) based on integrated reservoir model in the Niger Delta was develop for thin oil rim reservoirs using multivariable numerical optimization approach. The obtained result indicated that the developed correlation predicted 226.05 bbl/day compared to the actual Oilfield critical oil rate of 226.11 bbl/day. Furthermore, sensitivity study indicated that the developed correlation and the integrated reservoir model predictions of fractional well penetration (hp/h) and height below perforation - oil column (hbp/h) on critical oil rate (qc) were close and resulted in coefficient of determination (R2) of 0.9266 and 0.9525, Chi square (X2) of 0.539 and 0.655, and RMSE of 4.336 and 4.357. Additionally, the results depict that critical oil rate depends indirectly on fractional well penetration and directly on height above perforation for vertical wells. Therefore, to delay water-coning tendency in thin oil rim reservoirs these completion parameters are consideration in vertical wells to establish optimum critical oil rate during hydrocarbons production. Also, the developed correlation can be used as a quick tool to estimate critical oil rate of thin oil rim reservoirs in the Niger Delta.Â Â